Osservare e valutare le competenze trasversali per valorizzare il successo formativo nella scuola - Niewint Gori, Jessica; Mori, Sara (Studi sulla Formazione/Open Journal of Education, 2022)
This this work intents to focus on the debate discussing the relationship between merit and skills. Enhancing the role of feedback and extend the assessment of transversal skills to improve students’ educational success and the development of personal development. The tools proposed promote group work and feedback in the educational process and help teachers developing and applying design-based lesson units.